Exploratory studies on grain refinement in medium chromium ferritic stainless steel welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Information Engineering Research Institute (IERI), 2011)
The fusion welding of ferritic stainless steel is associated with several challenges principal among which is the grain coarsening in and around the weld section. This leads to loss in ductility and toughness. It may be possible to improve ductility in the ferritic weld if refined grain structure can be produced. Available literatures indicate that formation of refined grains in weld is promoted by ensuring low net heat input and faster transfer dynamics. This may be achieved by controlling the proportion of arc heat input that is actually delivered to the workpiece or enhancing the solidification process by artificially agitating the weld pool. Addition of elemental powder ex-situ as well as the use of cryogenic cooling offer means for controlling net heat input and ensuring faster cooling from the grain coarsening temperature. In the present work, exploratory studies are conducted on grain refinement in medium chromium ferritic stainless steel weld via ex-situ elemental powder addition and cryogenic cooling. It emerged from the study that grain refinement averaged 40% with cryogenic cooling, 35% with aluminum and titanium, 55%. The refinement from cryogenic cooling is due to the steep thermal gradient provided by the cooling liquid while ex-situ elemental powders provide sites for heterogeneous nucleation of equiaxed grains leading to higher microhardness value which is indicative of greater resistance to flow stress and a measure of strength.